Ecological differentiation and the evolution and maintenance of fynbos diversity - Slingsby, Jasper (Department of Biological Sciences, 2015)
Preserving the structure and functioning of ecosystems and the benefits they provide to society depends on our understanding of how biodiversity influences ecosystem function and which processes determine the composition and diversity of biological assemblages. Ecological, evolutionary and biogeographical processes interact to determine the genesis, maintenance and spatio-temporal arrangement of biodiversity. Here I investigate these processes in the Cape fynbos of South Africa by examining the diversification, biogeography and community assembly of a clade of reticulate-sheathed Tetraria species (Cyperaceae:Schoeneae).